THE IMPORTANCE OF CALCA AND ACE GENES IN THE PATHOGENESIS OF MIGRAINE (CAHIERS MAGELLANES-NS, 2024)
Abstract. Until now, the diagnosis of "migraine" is exclusively clinical, and any diagnostic tests are aimed only at excluding other causes of headache. Despite the availability of a large number of specific anti-migraine drugs, the therapy of patients with migraine is still not effective enough. A significant clinical problem is the chronification of migraine attacks and the development of chronic daily headache, which occurs in 1% of patients per year. At the same time, about 10% of patients with migraine in the population and 40-60% of patients seeking specialized headache centers are resistant to standard therapy. The article presents the results of our research on this issue.